Teaching–Learning Methods and Their Effectiveness in Bachelor-Level - Sapkota, Bishnu Prasad; Kandel, Krishna Prasad; Rimal, Sagun; Sedhai, Rita (Jana Adarsha Research Journal, 2026)
The present study investigates the teaching-learning method and its effectiveness at the bachelor’s level, focusing on BBS and B. Ed. programs in community campuses of the Chitwan district, Nepal. It adopts an explanatory sequential mixed-methods design: survey of 100 students and interviews with 24 faculty members, to explore current teaching practices, perceptions and challenges. Findings indicate that traditional class teaching is more prevalent in BBS program, while student-centered approaches like group discussions, project work, and group tasks are more common in B. Ed. program. B. Ed. students perceived that such approaches are more effective than BBS students on aspects of participation, understanding, critical thinking, application, and motivation, which is highly significant at (p < 0.01). Interviews with faculty members of BBS point out the limitations of class size, resources, and time constraint, which do not permit much student activity. In B. Ed. program, the faculty adopts constructivist, experiential learning pedagogy, which is facilitated by smaller class size, greater alignment with the curriculum, and greater use of technology. Based on the conclusion of the study, the effectiveness of the teaching and learning process depends on pedagogical practices and contexts. Encouraging student-centric learning activities, participation in education, use of technologies in the learning process, and capacity building of faculty members could enhance academic performance and lifelong learning skills of the students in the Nepalese community campuses at bachelor level.